Proceedings of ADVED 2020- 6th International Conference on Advances in Education 2020
DOI: 10.47696/adved.2020156
|View full text |Cite
|
Sign up to set email alerts
|

Digital Learning in Foreign Language Teacher Training in Higher Education: A Case Study

Abstract: The Community of Inquiry framework provides a model to design and implement online and blended learning effectively from a socio-constructivist perspective which conceives learning as socially constructed (Garrison

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…to understand what communication works best for online teaching and what challenges are encountered by the students and academics with online teaching and learning. The literature on COVID-19 suggests that there is a need for a comprehensive view of the pedagogy of online education that integrates technology to support teaching and learning (Carrillo & Flores, 2020;Carlon 2020, Bozkurt & Sharma 2020. "Teaching and learning online entails a specific process which is visible in the roles, competences and professional development approaches, as well as in the curriculum, pedagogy, assessment and the nature of interaction among the participants" (Carrillo & Flores, 2020: 467).…”
Section: Zulumentioning
confidence: 99%
See 2 more Smart Citations
“…to understand what communication works best for online teaching and what challenges are encountered by the students and academics with online teaching and learning. The literature on COVID-19 suggests that there is a need for a comprehensive view of the pedagogy of online education that integrates technology to support teaching and learning (Carrillo & Flores, 2020;Carlon 2020, Bozkurt & Sharma 2020. "Teaching and learning online entails a specific process which is visible in the roles, competences and professional development approaches, as well as in the curriculum, pedagogy, assessment and the nature of interaction among the participants" (Carrillo & Flores, 2020: 467).…”
Section: Zulumentioning
confidence: 99%
“…Researchers (Garrison, Cleveland-Innes & Fung, 2010;Gutierrez-Santiuste et al, 2015;Bozkurt, 2019;Bozkurt & Sharma, 2020, Carlon, 2020 have used the Col Framework to design and reflect on synchronous and asynchronous teaching and learning. A study conducted in Spain by Gutierrez-Santiuste et al (2015) used the CoI framework to analyse student communication in chats, forums and emails and find correlations among the three presences.…”
Section: Perspectives In Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on their findings, the researchers concluded that the utilization of social media and online learning technology needed to be explored more fully to effectively benefit from them in teaching and learning irrespective of whether they were implemented under unprecedented conditions such as the Covid-19 pandemic. Conducting a case study on digital learning in foreign language teacher training, Carlon (2020) scrutinized PSEFLT perceptions of the effectiveness of emergency remote education in a blended undergraduate course. He reported that participants acknowledged the effectiveness of teaching when opportunities for social interaction and cognitive involvement were implemented in the course.…”
Section: Introductionmentioning
confidence: 99%
“…Inpeng and Nomnian (2020), for example, primarily investigated the integration of Facebook into a Teaching English as a Foreign Language (TEFL) program to promote pre-service EFL teachers' English language literacy, pedagogical knowledge, and ICT skills. Carlon (2020), on the other hand, investigated students' perceptions on the effectiveness of emergency remote education implemented in a graduate course developed within the Community of Inquiry framework. The current study did not focus on an integration of social media platforms or methodological frameworks into ELT programmes, but was carried out with Turkish pre-service teachers of English as a foreign language at a Turkish state university where course attendance was not compulsory during the pandemic.…”
Section: Introductionmentioning
confidence: 99%